The Utilization of Bahal Portibi Temple as a Social Studies Learning Resource at SMPN 1 Halongonan - Titin Nurbani Siregar; Ponidi Ponidi (Universitas Muhammadiyah Enrekang, 2025)
This study aims to examine the use of the Bahal Portibi Temple as a source of Social Science (IPS) learning at SMP Negeri 1 Halongonan, North Padang Lawas Regency. The Bahal Temple is a historical heritage site with high educational value and great potential for integration into the contextual learning process. This study employs a descriptive qualitative approach, utilizing data collection techniques that include observation, interviews, and documentation. The study's results demonstrate that the Bahal Temple possesses historical, cultural, and architectural values that are highly relevant to support social studies learning, particularly in aspects of local history and culture. However, its use is still limited due to limited infrastructure, low teacher awareness, and a lack of support from educational institutions. Therefore, an integrative and collaborative strategy is needed between schools, the community, and the government to optimize the use of local historical sites as an effective and meaningful learning medium.